2021
DOI: 10.1123/jsep.2019-0313
|View full text |Cite
|
Sign up to set email alerts
|

A Moral Intervention Reduces Doping Likelihood in British and Greek Athletes: Evidence From a Cluster Randomized Control Trial

Abstract: Objectives: The authors aimed to develop a moral intervention and to determine whether it was more effective in preventing doping than an educational (i.e., knowledge-based) intervention; their primary outcome was doping likelihood, and the secondary outcomes were moral identity, moral disengagement, moral atmosphere, and anticipated guilt. Methods: Eligible athletes (N = 303) in the United Kingdom and Greece took part in the study. The authors randomly assigned 33 clubs to either the moral or the educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 51 publications
6
33
1
1
Order By: Relevance
“…Previously, these aspects of Bandura's (1991) theory have also been supported in research on doping in sport, and image and performance enhancing drug use in fitness contexts (Boardley et al, 2017;Hodge et al, 2013;Lucidi et al, 2004Lucidi et al, , 2008. Further, recent research demonstrated a moral intervention reduced athletes' MD, increased their anticipated guilt, and reduced their doping likelihood from pre-to post-intervention and at six-month follow-up (see below; Kavussanu et al, 2021). The present study suggests Bandura's (1991) theory may have relevance in a wider range of substance-use contexts than previously thought (i.e.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previously, these aspects of Bandura's (1991) theory have also been supported in research on doping in sport, and image and performance enhancing drug use in fitness contexts (Boardley et al, 2017;Hodge et al, 2013;Lucidi et al, 2004Lucidi et al, , 2008. Further, recent research demonstrated a moral intervention reduced athletes' MD, increased their anticipated guilt, and reduced their doping likelihood from pre-to post-intervention and at six-month follow-up (see below; Kavussanu et al, 2021). The present study suggests Bandura's (1991) theory may have relevance in a wider range of substance-use contexts than previously thought (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…One intervention targeting doping in Greek and UK athletes in late adolescence included activities targeting MD, moral identity, and moral atmosphere (i.e. group social norms; Kavussanu et al, 2021). The MD components presented stories of athletes who doped and used MD-based justifications for their actions.…”
Section: Discussionmentioning
confidence: 99%
“…The athletes’ study results provide rationale that strengthening the moral identity of athletes and, at the same time, promoting their anti-doping attitudes and internalization of moral values is important, which is in line with other research. A recent randomized control trial provides support that intervention not only involves knowledge about doping, but that moral values in sport also affect the moral identity of athletes [ 53 ]. On the other hand, it is not enough to limit oneself to sport-related values or to emphasize their importance in sport alone, especially in strengthening moral identity.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions were carried out in a diverse range of countries. Seven studies were conducted in the United States of America [41][42][43][44]48,54,56], five in the United Kingdom [45,47,50,51,53], three in Greece [35,47,53], two in Iran [33,46], two in Italy [37,49], one in Japan [36], Spain [34], Sweden [52], Germany [39], Malaysia [40], Australia [57], Canada [38], and Norway [55]. The sample size ranged from 35 to 20,800 and participants were older than 12 years of age.…”
Section: Intervention Demographicsmentioning
confidence: 99%